Analisis Profitabilitas Penggunaan Pakan Komplit Merek X dan Y pada Itik Petelur di PT Amar Farm Internasional - Zahra, Siti Kumala; Dewi, Intani (Universitas Batangahari Jambi, 2025)
Feed cost is the dominant component of production expenses in laying duck farming, accounting for approximately 60–70% of total production costs. PT Amar Farm Internasional has transitioned from using mixed feed to commercial complete feed. However, the complete feed used by the company tends to be relatively expensive in the Yogyakarta area. Therefore, the availability of more affordable feed from different brands has become a consideration in feed brand selection. This study aims: (1) to analyze the productivity of laying ducks fed with complete feed brand X and brand Y; and (2) measure the profitability of each feed brand to support the company's decision-making in feed selection. This research is an experimental study using a post-test only control group design. This research used two random groups; the treatment group received feed brand X (new feed), while the control group continued using feed brand Y (current feed). The analysis method applied was descriptive-quantitative, focusing on productivity and profitability aspects. The results indicated that feed brand X generated a higher profit compared to feed brand Y, with an average Gross Profit Margin (GPM) of 18.87% and Net Profit Margin (NPM) of 8.34% from August to December. Additionally, the average Duck Day Production (DDP) ranged from 0.32%-89.77%, the Feed Conversion Ratio (FCR) was 2.73, and the total number of eggs produced was 9,905. Hence, feed brand X is recommended as a replacement for brand Y in the current cycle, and for exclusive use in future production cycles.